Algebras of generalized dihedral type - Erdmann, K; Skowroński, A (Cambridge University Press, 2019)
We provide a complete classification of all algebras of generalized dihedral type, which are natural generalizations of algebras which occurred in the study of blocks of group algebras with dihedral defect groups. This gives a description by quivers and relations coming from surface triangulations.